Music Regulators in Two String Quartets: A Comparison of Communicative Behaviors between Low- and High-Stress Performance Conditions - Biasutti, Michele; Concina, Eleonora; Wasley, David; Williamon, Aaron (Frontiers in Psychology, 2016)
In ensemble performances, group members use particular bodily behaviours as a sort of “language” to supplement the lack of verbal communication. This research study focuses on music regulators, which are defined as signs to other group members for coordinating performance. The following two music regulators are considered: body gestures for articulating attacks (a set of movements externally directed that are used to signal entrances in performance) and eye contacts. These regulators are recurring observable behaviors that play an important role in nonverbal communication among ensemble members. To understand how these regulators are used by chamber musicians, video recordings of members of two string quartet ensemble performances (Quartet Ensemble A performing Bartók and Quartet Ensemble B performing Haydn) were analysed under two conditions: a low stress performance (LSP), undertaken in a rehearsal setting, and a high stress performance (HSP) during a live concert. The results provide evidence for more emphasis in gestures for articulating attacks (i.e. the perceived strength of a performed attack-type body gestures) during HSP than LSP. . Conversely, no significant differences were found for the frequency of eye contact between HSP and LSP. Moreover, there was variability in eye contacts during HSP and LSP, showing that these behaviours are less standardised and may change according to idiosyncratic performing conditions. Educational implications are discussed for improving interpersonal communication skills during ensemble performance.